2021
DOI: 10.1152/ajpgi.00186.2021
|View full text |Cite
|
Sign up to set email alerts
|

Role of circadian rhythm and autonomic nervous system in liver function: a hypothetical basis for improving the management of hepatic encephalopathy

Abstract: Hepatic encephalopathy (HE) is a common, incapacitating disease that affects many patients with cirrhosis. While several therapies have proven effective in the treatment and prevention of this condition, several patients continue to suffer from covert disease or episodes of relapse. The circadian rhythm has been demonstrated to be pivotal for many body functions, including those of the liver. Here, we explore the impact of circadian rhythm-dependent signaling on the liver and discuss the evidence of its impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 209 publications
0
23
0
Order By: Relevance
“…There is substantial evidence that impaired structure and function of liver tissues or cells can affect the function of other tissues and organs; for example, emerging changes in renal function in patients with acute or chronic liver disease often lead to acute kidney injury [ 161 ] or chronic kidney diseases [ 162 ]. Severe abnormalities in liver function can even damage the nervous system and cause central nervous system dysfunction, leading to the development of hepatic encephalopathy [ 163 ]. Abnormal liver function can also affect cardiac function, and patients with cirrhosis can develop increased left ventricular weight and left eccentric hypertrophy, leading to the development of cirrhotic cardiomyopathy [ 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that impaired structure and function of liver tissues or cells can affect the function of other tissues and organs; for example, emerging changes in renal function in patients with acute or chronic liver disease often lead to acute kidney injury [ 161 ] or chronic kidney diseases [ 162 ]. Severe abnormalities in liver function can even damage the nervous system and cause central nervous system dysfunction, leading to the development of hepatic encephalopathy [ 163 ]. Abnormal liver function can also affect cardiac function, and patients with cirrhosis can develop increased left ventricular weight and left eccentric hypertrophy, leading to the development of cirrhotic cardiomyopathy [ 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to establish and quantify cellular and whole organ patterns of variability and then implement them into the algorithm for improving accuracy [ 25 , 43 , 68 , 76 , 85 , 97 , 100 , 101 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 153 , 154 , 155 , 156 , 157 , 158 ]. Important information is also obtained by evaluating single-cell variabilities in gene expression, proteomics, metabolomics, and epitope expression performed on cells harvested from patients before and after therapy for chronic disease.…”
Section: A Three-phase Roadmap For Developing a Platform For Overcomi...mentioning
confidence: 99%
“…Recent studies described the development of a platform for overcoming drug resistance based on the following three phases [ 1 , 140 , 141 ]: introducing irregularity in therapeutic regimens for improving drug responsiveness; establishing a closed-loop algorithm for generating individualized patterns of irregularity to overcome drug resistance; upscaling the algorithm by implementing quantified personal variability patterns along with additional personalized signatures based on genes, proteins, and other disease or host relevant variables [ 1 , 25 , 43 , 68 , 76 , 85 , 98 , 99 , 100 , 101 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ].…”
Section: A Three-phase Roadmap For Developing a Platform For Overcomi...mentioning
confidence: 99%
“…Drug resistance is a significant health issue during chronic opioid use for pain [108]. Studies showed a similar resistance for many other drugs like anti-depressants, anti-diabetics, and diuretics [64,65,75,80,[102][103][104][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126].…”
Section: Overcoming Plateaus In Muscle Training By Introducing Subjec...mentioning
confidence: 99%
“…Second-generation artificial intelligence systems can implement variability into training and therapeutic regimens for overcoming biological tolerance and plateaus for various chronic diseases [80,[102][103][104][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. Introducing variability to improve muscle performance can be implemented in two stages.…”
Section: Overcoming Plateaus In Muscle Training By Introducing Subjec...mentioning
confidence: 99%